2020
DOI: 10.4014/jmb.2006.06022
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Leukemic Cells Induced by Anti-proliferative Coumarin Isolated from the Stem Bark of Fraxinus rhynchophylla

Abstract: Esculetin 6-O-β-D-arabinofuranosyl-(1 → 6)-β-D-glucopyranoside (EAG) is a coumarin glycoside isolated from the stem bark of Fraxinus rhynchophylla. This study scrutinized the anti-proliferative activity of EAG on blood cancer-derived Jurkat leukemic cells. Cell viability assays in leukemic cancer cells determined that EAG possesses potent anti-proliferative effects. Moreover, treatment with EAG increased the proportion of apoptotic cells, resulted in cell cycle arrest being induced at the subG0/ G1 phase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Icariin, a flavonoid isolated from Epimedium , was reported to inhibit the ovarian cancer cell proliferation, invasion and migration, likewise induce the cell apoptosis through AKT/Mtor/ATG5 signalling pathway 2 . Aescin, a coumarin glycoside compound isolated from the bark of the cane EAG, exhibited the anti‐proliferative activity towards Jurkat leukaemia cells through cell cycle arrest 3 . These studies indicated that the bioactive ingredients extracted from the TCM were promising resources, which could be utilized as nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Icariin, a flavonoid isolated from Epimedium , was reported to inhibit the ovarian cancer cell proliferation, invasion and migration, likewise induce the cell apoptosis through AKT/Mtor/ATG5 signalling pathway 2 . Aescin, a coumarin glycoside compound isolated from the bark of the cane EAG, exhibited the anti‐proliferative activity towards Jurkat leukaemia cells through cell cycle arrest 3 . These studies indicated that the bioactive ingredients extracted from the TCM were promising resources, which could be utilized as nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Esculetin, a coumarin derivative, reportedly has several biological and pharmacological activities, including antioxidant, anti-inflammatory, and antiedema effects [ 22 , 29 ]. Moreover, recent studies have reported the anticancer effects of esculetin against various human cancers, including lung cancer [ 30 , 31 ], colorectal cancer [ 27 , 32 , 33 ], gastric cancer [ 34 ], and leukemia [ 35 , 36 , 37 , 38 ]. In particular, it is noteworthy in the antitumor effect of esculetin in human breast cancer, the counterpart of canine mammary cancer.…”
Section: Discussionmentioning
confidence: 99%